Novel recombinant avian infectious bronchitis viruses from chickens in Korea, 2019–2021 - Kim, Hyun-Jin; Lee, Hyuk-Chae; Cho, Andrew Y.; Choi, Yun-Jeong; Lee, Heesu; Lee, Dong-Hun; Song, Chang-Seon (Frontiers in Veterinary Science, 2023)
Infectious bronchitis virus (IBV) has evolved through various mutation mechanisms, including antigenic drift and recombination. Four genotypic lineages of IBVs including GI-15, GI-16, GI-19, and GVI-1 have been reported in Korea. In this study, we isolated two IBVs, designated IBV/Korea/289/2019 and IBV/Korea/163/2021, which are natural recombinants between the S1 gene of K40/09 strain (GI-19 lineage) and IBV/Korea/48/2020 (GI-15 lineage) in different recombination patterns. Comparative sequence analysis of hypervariable regions (HVRs) revealed that the IBV/Korea/289/2019 strain had similar HVR I and II regions with the K40/09 strain, and HVR III region with the IBV/Korea/48/2020. In contrast, the IBV/Korea/163/2021 had HVR I and II regions similar to the IBV/Korea/48/2020, and HVR III to the K40/09 strain. The IBV/Korea/289/2019 exhibited similar pathogenicity, tissue tropism, and antigenicity with the parental K40/09 strain. The IBV/Korea/163/2021 exhibited similar pathogenicity and tissue tropism with the K40/09 strain, but different antigenicity with both parental strains. The continued emergence of the novel reassortant IBVs suggests that multiple recombination events have occurred between different genotypes within Korea. These results suggest that antigenic profiles could be altered through natural recombination in the field, complicating the antigenic match of vaccine strains to field strains. Enhanced surveillance and research into the characteristics of newly emerging IBVs should be carried out to establish effective countermeasures.